Pluralitas Mazhab dalam Fikih - M. Gazali Rahman (Al-Ulum, 2010)
This paper describes why Indonesian Muslims are polarized in a different understanding of the shari'a law. Recently, brotherhood and unity among Muslims considered still hazardous and agonizing. Despite the fact that the difference among the Muslims is about the matters of furu'iah; yet, its implication becomes widening and reaching other significant aspects such as determination of various legal provisions concerning the dimensions of faith, worship, and social life. In order to increase awareness and development of Muslim brotherhood, there have to be concern on maintaining condition ukhuwah cultures, patience, inclusiveness, and acknowledgement of the truth. Muslims also are supposed to not impose a uniformity that does not or has not received by other parties, and endorse similarities that exist of any differences.